2005
DOI: 10.1890/04-1613
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Mortality Increases With Clutch Size in a Neotropical Bird

Abstract: Abstract. The change in avian clutch size with latitude is a celebrated example of geographic variation in a vertebrate life-history trait. Alternative hypotheses for this pattern invoke nest predation, limited food for nestlings, or post-fledging juvenile mortality as selection pressures leading to small clutch size of tropical birds. We manipulated the clutch size of Spotted Antbirds (Hylophylax naevioides) in central Panama to test these hypotheses. We observed that rates of nest predation were not influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 27 publications
(35 reference statements)
0
44
0
Order By: Relevance
“…This presumably could be influenced by parental investment, and periods of postfledging care tend to be longer in tropical than in temperate regions (Ricklefs 1969b;Styrsky et al 2005). Little is known about survival during that period, however.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This presumably could be influenced by parental investment, and periods of postfledging care tend to be longer in tropical than in temperate regions (Ricklefs 1969b;Styrsky et al 2005). Little is known about survival during that period, however.…”
Section: The Modelmentioning
confidence: 99%
“…Thus, with respect to decisions concerning individual acts, f might be very small. Most applications of Williams's principle have addressed questions such as the optimum time to , 1995Martin et al 2000aMartin et al , 2000bGhalambor and Martin 2001) and birds are exquisitely sensitive to the presence of predators (Briskie et al 1999;Ghalambor and Martin 2002;Fontaine and Martin 2006;Fontaine et al 2007), quantitative models (Ricklefs 1977a) and experimental studies (Young 1996;Styrsky et al 2005) provide little support for this mechanism, which will not be considered further here.…”
Section: Introductionmentioning
confidence: 99%
“…Further research has revealed that several other aspects of avian life history also depend on latitude (Ricklefs 2000a;Martin et al 2006). Birds that breed near the equator ("tropical birds") care for their young for a long time (Russell 2000;Schaefer et al 2004;Styrsky et al 2005). Young tropical birds tend to have slow growth rates (Ricklefs 1976;Bryant and Hails 1983), they do not become mature as soon as the young of nontropical species (Skutch 1976;Russell 2000;Russell et al 2004), and senescence is delayed (Møller 2007).…”
mentioning
confidence: 99%
“…However, direct comparisons of the frequency and intensity of begging vocalizations on rate of nest predation have produced varying results (Leech andLeonard 1997, Halupka 1998). Moreover, experimental manipulation of brood size and activity levels in two tropical species failed to establish a relationship between activity and probability of predation (Young 1996, Styrsky et al 2005. Thus, although predators undoubtedly influence the evolution of parental behavior at the nest, including nest structure and placement (Fontaine et al 2007), it is as yet unclear whether predation pressure selects for reduced nest attendance and reduced brood size in tropical birds.…”
Section: Discussionmentioning
confidence: 99%
“…He argued that predators cue in on begging by chicks or parental activity near nests, and that more activity leads to greater probability of nest predation. This long-standing hypothesis has been evaluated by comparing rates of predation during the incubation and nestling periods (Ricklefs 1969, Roper and Goldstein 1997, Farnsworth and Simons 1999 and subsequent to experimental manipulation of brood size (Young 1996, Styrsky et al 2005. Results to date are not definitive, but they have confirmed neither that activity at nests increases nest predation, nor that reduced parental investment in response to predation risk is responsible for the small clutches of tropical birds (Ricklefs 1977).…”
mentioning
confidence: 99%